Konsep Keseimbangan dalam Ekonomi Islam: Antara Rasionalitas dan Spiritualitas - Abdul Wahab (Al-Buhuts, 2022)
Islamic economic values are not determined based on rational measurements such as capitalism, liberalism, and others. The economy will not work Islamically without rational dan spiritual equivalence. Therefore, the role of the mind and heart is considered crucial to implementing economic activities from an Islamic perspective. If the economics do not acquire both of them, they potentially would face some distortions. There is nothing more special between mind and heart in carrying out economic activities, where the mind is applied to thinking properly and correctly (rational), while the heart is used to notify faith situations (spiritual). So that Islamic values be able to obtain only if there is a balance between rational and spiritual. This study aims to provide an overview of the role of Islamic economics. The literature study approach is used in this work in which data would be collected by reviewing findings, while secondary data from books, journals, articles, and other works of literature is the data that would be processed. This paper shows that the role of Islamic economics could only be apprehended if there is an equivalent of rationality and spirituality.